- Examination of Technical Factors Influencing Building Maintenance in the Post-Retention Period - Putra, Moch. Maulana Kurnianda Saputra; I Nyoman Dita Pahang Putra (Jurnal Civil Engineering Study, 2025)
Building maintenance is essential for ensuring structural sustainability, especially during the post-retention period when responsibilities shift to the owner. This study analyzes the influence of six technical factors—building design, maintenance frequency, material availability, weather adaptation, material quality, and quality control—on maintenance success. A quantitative approach with Structural Equation Modelling (SEM) was used, based on 50 expert responses. Results show all six factors significantly affect maintenance success, material quality was identified as the most dominant indicator within the technical factors construct, with a loading factor score of 0.784. Of the success indicators—cost, time, quality, user safety health and security, and durability—quality assurance is the most dominan with a loading factor score of 0.841. The model explains 61.8% of variance (R² = 0.618), demonstrating strong predictive relevance. These findings underscore the importance of integrating high-quality materials, applying strict quality control, and employing strategic planning. The study offers practical insights for building owners and contractors during the post-retention phase. Future research may expand on technological and environmental considerations for better maintenance outcomes.